Konsep Filsafat Ilmu dalam Perspektif Islam dan Barat - Sarwanto, Sarwanto; Pramono, Agus; Z, M. Badruddin; Yulianto, Rahmat (Lembaga Yasin AlSys, 2026)
Philosophical studies of science in Western and Islamic traditions have been widely discussed; however, research that specifically analyzes the fundamental differences in the sources, methods, and aims of knowledge between these two civilizations remains limited. This study aims to identify the fundamental differences in the ontological foundations (the nature of the existence of knowledge), epistemological foundations (sources and means of acquiring knowledge), and axiological foundations (values and purposes of knowledge) within the framework of Western and Islamic philosophy of science. The study employs a comparative analytical method on key concepts in the philosophy of science by examining the relationships between sources of knowledge, the operation of reason and empirical experience, and the value orientations that underlie the aims of scientific development in each tradition. The findings indicate that the Western perspective tends to be dominated by secularism, characterized by the separation of knowledge from religious values, an emphasis on reason and the senses as the primary sources of knowledge, and an orientation of scientific aims toward material progress and the fulfillment of worldly needs. Conversely, in the Islamic perspective, the philosophy of science is grounded in the principle of tauhid, which integrates knowledge with religious teachings; the sources of knowledge encompass not only reason and the senses but also Al-Qur'an and Hadis as the highest sources of truth and guides for human thought, with a more holistic orientation aimed at understanding the greatness of Allah SWT, attaining well-being in this world and the hereafter, and forming morally virtuous human beings. In conclusion, these differences in ontological, epistemological, and axiological frameworks demonstrate that although both traditions produce knowledge, their philosophical foundations and ultimate goals are markedly distinct, thereby providing a more comprehensive understanding of the position and function of knowledge in Western and Islamic civilizations.